The enhancement of gamification leader board model based on player type to increase learning engagement - Daud, Rafizah (2019)
Gamification is gaining energy as an educational innovation to engage students in their learning process. Education can benefit from gamification by improving learning environment to make it more enjoyable and engaging for students. Initial study indicated that leader board is one of the most popular gamification elements. However, the design of the leader board must be carefully balance since the lower position in the scoreboard can possibly affect engagement in a negative way. Some researches highlighted that some of the students enjoyed the competition and some of them did not. Hence, the aim of this study was to develop a gamification leader board model based on player type (GLeb) to engage students learning. This study involved both quantitative and qualitative methods. The quasi experiment three separate-sample pretest-posttest design was adopted to test the usability of GLeb prototype. The instruments used in this study were pre and post test, classroom observation rubric and perception of gamification leader board model based on player type. A total of 55 students from three Community Colleges in Melaka had involved in this study. The data were analyzed using descriptive, parametric and Partial Least Squares Structured Equation Model (PLS-SEM). The results show that the GLeb model contributes towards positive effect mediated by learning interaction in increasing learning engagement. The deployment of game mechanics produced greater learning engagement in quality of task, task completion time and task download time. The findings of this study are aligned with the Theory of Gamified Learning. Among key recommendations for future study are to refine the proposed model for affective engagement component and to further explore other potential elements of gamification to retain students’ engagement. In conclusion, the formation of the GLeb could provide guidelines and conceptual model for Massive Open Online Courses (MOOC) Developers or other Learning Management Systems (LMS) to implement gamification design based on player type.